Integration of Sr0.8Bi2.2Ta2O9/HfO2 ferroelectric/dielectric composite film on Si substrate for nonvolatile memory applications. Issue 4 (27th December 2019) - Jha, Rajesh Kumar; Singh, Prashant; Goswami, Manish; Singh, B. R.
Abstract: Sr0.8 Bi2.2 Ta2 O9 (SBT) ferroelectric and HfO2 dielectric layers were successively deposited onto the p-type (100) Si substrate via RF sputtering. Metal-Ferroelectric-Insulator-Silicon (MFIS) capacitors were fabricated with 200 nm SBT and 10 nm HfO2 film shows the improved memory window of 1.811 V as compared to the 1.27 V in Metal-Ferroelectric-Silicon (MFS) structures. Improvement in leakage current and breakdown voltage was also observed in the MFIS structures as compared to the MFS structures. Degradation of ferroelectric polarization was not pronounced even after applying 8 × 10 12 bipolar cycles in MF(200nm) I(10nm) S structures and the device shows significant data retention time of more than 2.5 hours.